Knowledge, Attitudes, and Practices on Do-It-Yourself (DIY) Braces among Public Senior High School Students in Manila S.Y. 2019-2020/Erynne Richelle T. Ongchan. - Ongchan, Erynne Richelle T.; Alfaro, Arlene Cecilia A. (2024)
INTRODUCTION: It is during the adolescent stage (ages 10-19 years old), that individuals are most concerned about their physical appearance. Dental braces are fixed appliances used in orthodontics which help correct misaligned teeth to improve function, esthetics, and overall dental health. As early as 2015, DIY braces/ fashion braces have emerged in the Philippines. There are several warnings and reports on the dangers of using DIY braces/ fashion braces in various media outlets, but there are still a number of people who avail of them. In order to understand this trend, this research attempts to determine adolescents’ knowledge, attitudes, and practices towards dental braces and DIY braces.
METHODOLOGY: Senior high school students in one public school in Manila S.Y. 2019-2020 participated in the analytical cross-sectional study (n=288). Data were collected using self-administered questionnaires to determine their knowledge, attitudes, and practices toward DIY braces.
RESULTS: Most (86.8%) of the participants stated that they knew what dental braces are, however they only had a mean score of 6.536 out of 9 which only shows fair knowledge. Among participants, 56% demonstrated good knowledge, and majority
x
(86%) answered correctly when dental braces were related to esthetics. Only 35.2% were aware of DIY braces, mostly through media (64.7%). Only 67% recognized the difference between DIY braces and professionally installed dental braces and were aware of the harmful effects of improper use. Almost no one disagreed that dental braces should be installed by dentists, 3 out of 250 (1.2%). Several of those who are aware of DIY braces 29 out of 88 (33%), however believed that DIY braces are the same as dental braces installed by the dentist. Most participants (62.8%) sought orthodontic treatment to attain straight teeth, while 30.8% aimed to improve dental health. Esthetics was the primary motivator for seeking orthodontic treatment. Out of 288 participants, only 14 have/had dental braces, and none used DIY braces. The association between knowledge, attitudes and practices cannot be determined from the survey tool used.
CONCLUSION: Public senior high school students show good knowledge of dental braces, but lack knowledge on DIY braces. Their motivation for orthodontic treatment is mainly aesthetic. None were found to have DIY braces, indicating a potential area for education and intervention.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Braces .; Malocclusion